An evaluation of management effectiveness of China's marine protected areas and implications of the 2018 Reform. (May 2022) - Zhao, Yiyi; Pikitch, Ellen K.; Xu, Xiangxin; Frankstone, Timothy; Bohorquez, John; Fang, Xu; Zheng, Jie; Li, Yunyi; Chen, Zhu; Lin, Wuying; Hu, Wenjia; Xue, Guifang (Julia)
Abstract: Marine protected area (MPAs) and other effective area-based conservation measures (OECMs) have been crucial in protecting endangered species and habitats for sustainable ecosystem and marine biodiversity. China has nearly six decades of experience in the practice of MPAs. However, the management effectiveness of China's MPAs has been impeded by issues accumulated over the years. In 2018, the Chinese government embarked on a major institutional reform (2018 Reform) to upgrade its MPAs into natural protected area (NPA) system. This strategic decision and subsequent actions in transforming the existing protected areas (marine and terrestrial) to NPAs have brought substantial changes with significant implications towards an ecosystem-based management approach of China's national system for marine conservation. Based on the investigation of 27 representative MPAs and OECMs across the country, this study used 12 performance indicators to evaluate the management effectiveness of China's MPA system, and identified key issues affecting the effective operation of the system. The results indicated that the major issues hampering management effectiveness include multiple management agencies, lack of systematic planning for classification and zoning, lack of unified and specific legal system, and insufficient financial supports. On this basis, we examined new policy directives and work in progress relating to the reform, highlighted major changes to illustrate the extent to which the key issues being addressed, and pointed out the implications of the 2018 reform towards an ecosystem-based management approach and China's national effort towards global goals of conserving marine biodiversity. Highlights: China's MPAs generated conservation benefits but hampered by ineffective management. Fragmented management and weak enforcement can impede management effectiveness. 2018 State Council Institutional Reform unifies and streamlines management agencies. 2018 Reform consolidates MPAs, simplifies zoning, and unifies new legal system. Operation supports for fund and research are needed to meet conservation objectives.